(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
The hospitality industry, especially the hotel sector, is one of the world’s highest in staff turnover rate. This is also the case in Indonesia, where the hotel industry is rife with problems related to high staff turnover. In this paper, we explore how hotel employees view the meaning of their work and how it contributes to their work engagement, organizational commitment, and turnover intention. Based on the data collected from 406 hotel employees in Jakarta and Bali, a structural equation model (SEM) was used to examine if hotel employees’ meaning of work influences their engagement with their work, commitment to the organization, and turnover intention. The results indicated that employees’ meaning of work positively influenced work engagement, and work engagement positively influenced organizational commitment. Work engagement was found to be an indirect-only mediator in the relationship between meaning of work and organizational commitment. Additionally, organizational commitment was also found to negatively influenced turnover intention. As the first study of its kind in Indonesia, this paper provides an invaluable starting point for examining the dynamics of meaningful work with employee engagement, commitment, and turnover in Indonesian hotel employees.